Repeated sprint training improves intermittent peak running speed in team-sport athletes - Hunter, J. R.; O'Brien, B. J.; Mooney, M. G.; Berry, J.; Young, W. B.; Down, N. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to compare the effect of 2 repeated sprint training interventions on an intermittent peak running speed (IPRS) test designed for Australian Rules football. The test required participants to perform 10 × 10-m maximal efforts on an 80-m course every 25 seconds, for each of which the mean peak speed (kilometers per hour) was recorded to determine IPRS. The training interventions were performed twice weekly for 4 weeks immediately before regular football training. In the constant volume intervention (CVol), sprint repetition number remained at 10 (n = 9), and in the linear increase in volume (LIVol) intervention, repetition number increased linearly each week by 2 repetitions (n = 12). Intermittent peak running speed, 300-m shuttle test performance, and peak running speed were assessed before and upon completion of training. All measures were compared to a control group (CON; n = 8) in which players completed regular football training exclusively. Intermittent peak running speed performance in CVol and LIVol improved significantly (p < 0.01) by 5.2 and 3.8%, respectively, with no change in IPRS for CON. There were no differences in IPRS changes between CVol and LIVol. Additionally, peak running speed improved significantly (p < 0.01) by 5.1% for CVol, whereas 300-m shuttle performance improved significantly (p < 0.01) by 2.6% for LIVol only. Intermittent peak running speed, 300-m shuttle performance and peak running speed were improved after 4 weeks of training; however, progressively increasing sprint repetition number had no greater advantage on IPRS adaptation. Additionally, exclusive regular football training over a 4-week period is unlikely to improve IPRS, peak running speed, or 300-m shuttle performance.